High-strength and high-toughness R-T-B rare earth permanent magnet and preparation method thereof

By refining the precipitates and uniformly distributing Ti3Nb precipitates, the problem of insufficient mechanical properties caused by the brittle materials of R-T-B rare earth permanent magnets is solved, and high-strength and high-toughness R-T-B rare earth permanent magnets are prepared, which are suitable for high-load scenarios.

CN119230231AInactive Publication Date: 2024-12-31HANGZHOU DIANZI UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411154948.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Due to the brittle material properties, R-T-B rare earth permanent magnets are prone to brittle breakage, resulting in poor mechanical properties and cannot meet the needs of high-load scenarios such as high-speed motors and electric vehicles.

Method used

By refining the size of the precipitates, the dispersion of the precipitates is improved, the growth of the main phase grains is inhibited, and the Ti3Nb precipitates are uniformly distributed in the magnet. SC sheets are prepared by vacuum induction smelting and belt-shing, and high-temperature heat treatment and unsaturated absorption are carried out. Hydrogen, gas flow grinding, molding and segmented vacuum sintering are used to prepare high-strength and high-toughness R-T-B rare earth permanent magnets.

Benefits of technology

It significantly improves the strength and toughness of the magnet, inhibits the overgrowth of the main phase grain, enhances the grain boundary phase, improves magnetic performance, and is suitable for high load and high impact scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230231A_ABST
    Figure CN119230231A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and high-toughness R-T-B rare earth permanent magnet and a preparation method thereof. Two high-melting-point elements of Ti and Nb are synergistically added, the ratio of the two elements is adjusted, SC sheet high-temperature heat treatment, unsaturated hydrogen absorption and segmented vacuum sintering are combined, generation of a fine-size Ti3Nb phase is promoted, precipitation of a large-size high-melting-point element boride is inhibited, fine-size Ti3Nb precipitate particles have better dispersivity, and the high-melting-point Ti3Nb-based composite material is prepared. When the R-rich phase is uniformly distributed on the grain boundary of the magnet, the grain boundary phase of the magnet can be effectively enhanced, meanwhile, main phase distortion is not caused, the hardness of the magnet is reduced, the strength and toughness of the magnet are improved, and therefore the magnet with high strength and high toughness is prepared, and the magnetic performance of the magnet is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-strength and high-toughness RTB rare earth permanent magnet and a preparation method thereof, belonging to the field of rare earth magnets. Background Art

[0002] As a functional material, the research on RTB rare earth permanent magnets has always focused on how to further improve their magnetic properties. In recent years, with the gradual expansion of the application field of RTB magnets, especially with the development of high-speed motors and their application in the field of electric vehicles, the requirements for their mechanical properties are getting higher and higher.

[0003] RTB rare earth permanent magnet is a brittle material, which is prone to brittle fracture when subjected to stress, which seriously restricts the use environment of the material. The main reasons for the poor mechanical properties of RTB rare earth permanent magnets are as follows: first, the main phase of the magnet is a complex intermetallic compound that cannot slip or twin deformation, so it is easy to brittle fracture when subjected to stress; second, the strength of the grain boundary R-rich phase is low and the ability to resist crack propagation is poor, so cracks are easy to propagate along the grain boundary R-rich phase; finally, RTB magnets have the characteristics of uneven microstructure, uneven grain size of the main phase and uneven distribution of the grain boundary R-rich phase, which easily lead to stress concentration.

[0004] Second phase strengthening is a common method to enhance the mechanical properties of RTB magnets. In current engineering practice, high melting point elements such as Zr, Ti and Nb are usually added to magnets and react with B to form borides. However, most high melting point element borides are large-sized strip / rod-shaped precipitates with poor dispersibility in magnets. Although they can improve the strength of the magnet, the improvement in the toughness of the magnet is limited. It is necessary to develop RTB rare earth permanent magnets with both high strength and high toughness to broaden the application areas of RTB magnets, which are suitable for both high-load scenarios and high-impact or repeated load-bearing situations. Summary of the invention

[0005] In view of the shortcomings of improving the mechanical properties of traditional RTB magnets, the present invention provides a high-strength and high-toughness RTB rare earth permanent magnet and a preparation method thereof. The present invention improves the strength and toughness of the magnet by refining the size of the precipitates and improving the dispersibility of the precipitates. At the same time, more finely dispersed precipitates can more effectively inhibit the growth of the main phase grains, and improve the magnetic properties of the magnet by refining the main phase grains.

[0006] The technical solution adopted by the present invention is: A high-strength and high-toughness RTB rare earth permanent magnet, the magnet composition comprises the following components: R: 28.5wt.%~34.0wt.%, R includes one or more elements selected from Nd, Pr, Dy, Tb, Ho, Gd, La, Ce, Lu, and Y; and R contains at least R1 element, and the R1 element is one or more of Nd, Pr, and Ce; B: 0.85~1.1wt.%, Ti: 0.1~0.4wt.%, Nb: 0.05~0.5wt.%, M: 0.01-8.0wt.%, M is at least one of Al, Cu, Ga, Ni, Zn, Sn, Mn, and Zr, The balance is T and other unavoidable impurities, where T is Fe or Fe and Co, and more than 85.0% of the mass fraction of T is Fe. And satisfy: [Ti] / 47.87≤4×[Nb] / 92.91, wherein [Ti] is the content of Ti expressed in mass fraction, and [Nb] is the content of Nb expressed in mass fraction; The magnet contains Ti3Nb precipitates, and more than 99% of the Ti3Nb precipitates are distributed in the R-rich phase at the grain boundaries of the magnet.

[0007] Furthermore, the size of the Ti3Nb precipitate is between 2 and 800 nm, preferably between 10 and 100 nm.

[0008] The Ti3Nb precipitates are distributed in the two-phase grain boundary and the multi-phase grain boundary of the magnet. The two-phase grain boundary is a grain boundary phase between two main phase particles, and the multi-phase grain boundary is a grain boundary phase surrounded by three or more main phase grains.

[0009] The magnet includes high melting point element precipitates, and the high melting point element precipitates include Ti3Nb precipitates and borides of Ti and Nb. In the magnet of the present invention, the amount of borides of Ti and Nb in a cross section of the magnet in any direction is less than 5% of the amount of high melting point element precipitates.

[0010] Furthermore, the high-strength and high-toughness RTB rare earth permanent magnet is prepared according to the following method: raw materials are taken according to the ratio to prepare SC sheets through vacuum induction melting and belt spinning, the SC sheets are subjected to high-temperature heat treatment, the SC sheets after high-temperature heat treatment are subjected to hydrogen cracking treatment for unsaturated hydrogen absorption, and air flow grinding to obtain alloy powder, the alloy powder is molded in an oriented magnetic field and cold isostatically pressed, and the obtained molded magnet is subjected to segmented vacuum sintering and aging treatment to obtain the high-strength and high-toughness RTB rare earth permanent magnet.

[0011] The present invention also provides a method for preparing a high-strength and high-toughness RTB rare earth permanent magnet, the method comprising: taking raw materials according to a ratio and preparing SC sheets through vacuum induction melting and belt spinning, performing high-temperature heat treatment on the SC sheets, performing hydrogen cracking treatment for unsaturated hydrogen absorption and air flow grinding on the SC sheets after the high-temperature heat treatment to obtain alloy powder, molding the alloy powder in an oriented magnetic field and performing cold isostatic pressing, and performing segmented vacuum sintering and aging treatment on the obtained molded magnet to obtain the high-strength and high-toughness RTB rare earth permanent magnet.

[0012] Furthermore, the high temperature heat treatment of the SC sheet means that the SC sheet is kept in an argon environment at 800-900° C. for 20 min-50 min, and the argon pressure is 30-50 kPa.

[0013] Furthermore, the unsaturated hydrogen absorption means that the number of hydrogen absorption is 0.2 to 0.8 times (preferably 0.3 to 0.5 times) the number of saturated hydrogen absorption; the saturated hydrogen absorption number is obtained by testing according to the following method: SC sheets of the same specification and weight are placed in a reactor, and after evacuation, hydrogen is filled with a positive pressure of 0.1 MPa, and the positive pressure refers to the difference between the absolute pressure and the standard atmospheric pressure. The SC sheet absorbs hydrogen, resulting in a decrease in the hydrogen pressure in the reactor, and the positive pressure in the reactor is reduced to 0.05 to 0.06 MPa. Hydrogen is filled into the reactor again until the positive pressure is 0.1 MPa, and each hydrogen filling action is counted as one hydrogen absorption number; after multiple hydrogen absorptions, after a certain hydrogen filling, the pressure change within 10 minutes is less than 0.5%, indicating that the SC sheet is saturated with hydrogen absorption, and the total number of hydrogen fillings at this time is the saturated hydrogen absorption number.

[0014] The segmented vacuum sintering includes low temperature segment sintering and high temperature segment sintering. The low temperature segment sintering is to keep the magnet at 900-1020°C for 3-6 hours, and the high temperature segment sintering is to keep the magnet at 1040-1080°C for 3-6 hours. The vacuum degree of the segmented vacuum sintering is 10 -4 Below Pa.

[0015] Furthermore, the vacuum induction melting and belt spinning method for preparing SC sheets generally involves melting raw materials into alloy liquid at 1480-1510° C., and pouring the molten alloy liquid through a tundish onto a rotating copper roller at 1440-1460° C. for solidification to obtain the SC sheets.

[0016] Furthermore, the vacuum induction melting and strip spinning are preferably carried out according to the following steps: raw materials with a purity of more than 99.9% are taken according to the composition ratio, and are placed in a crucible in descending order of melting point, and the furnace is evacuated until the vacuum degree reaches 10 -3 ~10 -4Pa, dew point is lower than -50℃; then fill the furnace with argon gas to make the gas pressure reach 30kPa~50kPa, and heat it to 1480~1510℃, and keep it warm for 3~5min after the raw materials are completely melted; then reduce the alloy liquid temperature to 1440~1460℃, pour the molten alloy liquid through the tundish onto the rotating copper roller for solidification, and obtain SC sheet. The process of belt casting is generally as follows: adjust the copper roller speed to 70~75 rpm, and then rotate the crucible at a certain speed, so that the molten alloy liquid is transported to the cooling roller through the tundish for solidification and then falls onto the water cooling plate for cooling, and obtains SC sheet.

[0017] The process of high temperature heat treatment of the SC sheet is generally carried out in the following steps: placing the SC sheet obtained by melting in a molybdenum boat, and then placing it in a heating furnace; drawing the vacuum degree in the furnace to 10 -3 ~10 -4 Pa and heat to 800~900℃. When the temperature reaches the target temperature, fill the furnace with argon gas at a pressure of 30~50kPa and keep it warm for 20min~50min. After the heat treatment is completed, cool it to room temperature. This process has no requirements on the cooling speed, and can use either furnace cooling or air cooling.

[0018] The hydrogen destruction treatment of the unsaturated hydrogen absorption is carried out according to the following steps: the SC sheet after high-temperature heat treatment is placed in a reactor, and after vacuuming, hydrogen is filled with a positive pressure of 0.1Mpa. The positive pressure refers to the difference between the absolute pressure and the standard atmospheric pressure. The hydrogen absorption of the SC sheet causes the hydrogen pressure in the reactor to decrease, and the positive pressure in the reactor is reduced to 0.05-0.06MPa. Hydrogen is filled into the reactor again until the positive pressure is 0.1MPa. Each hydrogen filling action is counted as one hydrogen absorption number; the hydrogen absorption number of unsaturated hydrogen absorption is 0.2-0.8 times the saturated hydrogen absorption number; the saturated hydrogen absorption number is obtained through pre-testing, which means that after SC sheets of the same weight specification have absorbed hydrogen multiple times, after a certain hydrogen filling, the pressure change within 10 minutes is less than 0.5%, indicating that the SC sheet is saturated with hydrogen absorption, and the total number of hydrogen fillings at this time is the saturated hydrogen absorption number. After the hydrogen absorption reaction is completed, the temperature is raised to between 400 and 600°C while evacuating the vacuum, and kept warm for 2 to 6 hours to release the hydrogen in the alloy sheet, and then cooled to obtain hydrogen-crushed coarse powder.

[0019] The jet milling process is carried out according to the following steps: the hydrogen-crushed coarse powder is placed in the jet milling equipment, and in an inert gas atmosphere, the nozzle pressure is adjusted to between 0.6MPa and 0.8MPa, and the coarse powder is driven by high-speed gas to collide with each other for crushing. The inert gas is generally helium, nitrogen and other inert gases.

[0020] Lubricants and / or antioxidants can be added to the alloy powder before molding, and conventional commercially available magnetic powder protection lubricants or antioxidants can be used. The amount of lubricant added can be 0.01-0.1% of the mass of the alloy powder, and the amount of antioxidant added can be 0.01-0.14% of the mass of the alloy powder.

[0021] The alloy powder is preferably molded in the orientation magnetic field according to the following steps: the orientation magnetic field is preferably 3-6T, and the molding pressure is 5-7MPa. The green compact after orientation molding is then cold isostatically pressed at a pressure of 150-180MPa. The density of the green compact after orientation molding is 3.6-4.0g / cm 3 The density of the green compact after cold isostatic pressing is about 4.5~4.6g / cm 3 Whether to perform cold isostatic pressing after molding can be selected according to the process. The present invention selects to perform cold isostatic pressing on the green compact after orientation molding to further eliminate cracks inside the green compact.

[0022] The segmented vacuum sintering includes two stages of sintering, low temperature and high temperature. The low temperature stage sintering is to keep the magnet at 900-1020° C. for 3-6 hours, and the high temperature stage sintering is to keep the magnet at 1040-1080° C. for 3-6 hours.

[0023] The aging treatment refers to a primary aging treatment process in which the sintered magnet is subjected to a temperature of 700-900°C for 2-8 hours, then cooled to below 100°C at a rate of not less than 20°C / min, and then heated to 400-600°C for a secondary aging treatment of 2-8 hours, and then cooled to below 80°C at a rate of not less than 30°C / min.

[0024] Second phase strengthening is a common method to enhance the mechanical properties of RTB magnets. In current engineering practice, high melting point elements such as Zr, Ti and Nb are usually added to magnets and react with B to form borides. However, most high melting point element borides are large-sized strip / rod-shaped precipitates with poor dispersibility in magnets. Although they can improve the strength of the magnet, they have limited improvement in the toughness of the magnet. The present invention rationally regulates the composition of the magnet so that the magnet contains 0.1~0.4wt.% Ti and 0.05~0.5wt.% Nb, and at the same time, the content of Ti and Nb satisfies [Ti] / 47.87≤4×[Nb] / 92.91, where [Ti] is the content of Ti expressed in mass fraction, and [Nb] is the content of Nb expressed in mass fraction. Combined with SC sheet heat treatment, the formation of Ti3Nb phase in the magnet is promoted and the precipitation of Ti and Nb borides is inhibited. Since the Ti3Nb precipitates are small in size and better dispersed in the magnet, they can more effectively improve the strength of the magnet and increase the toughness of the magnet.

[0025] The present invention performs a high-temperature short-time heat treatment on the melt-spun SC sheet to promote the nucleation and initial growth of Ti3Nb in the SC sheet. Experiments show that the initial formation temperature of Ti3Nb is about 800°C or above. In order to ensure that the Ti3Nb phase precipitates do not grow excessively in the spun sheet, the high-temperature heat treatment temperature used in the present invention is 800-900°C, and the heat preservation is 20-50 minutes. At the same time, in order to prevent the SC sheet from oxidation and the rare earth from volatilizing under high temperature conditions, argon protection is used during the heat treatment of the SC sheet, and the pressure of the argon gas is 30-50kPa.

[0026] The hydrogen breaking process of the SC sheet is a hydrogen absorption and expansion process of the grain boundary phase and the main phase. In order to prevent the excessive crushing of the grain boundary phase during the hydrogen breaking process, which leads to a large loss of Ti3Nb compounds distributed in the grain boundary phase during the airflow milling stage as the ultrafine powder is separated, the hydrogen crushing in the present invention adopts an incomplete hydrogen absorption process. During conventional saturated hydrogen crushing, the hydrogen pressure in the reactor is generally 0.01~0.09MPa. During the hydrogen absorption reaction, the change in the internal pressure of the reactor within 10 minutes does not exceed 0.5%, which represents saturated hydrogen absorption. In the present invention, an unsaturated hydrogen absorption process is adopted, and the number of hydrogen absorptions is 0.2~0.8 times the normal saturated hydrogen absorption number. After subsequent airflow milling, the fine Ti3Nb precipitate particles are evenly mixed with the magnetic powder.

[0027] In the present invention, the magnet sintering process includes two stages of sintering, low temperature and high temperature. In order to improve the grain refinement effect of Ti3Nb precipitates, the magnet green body is first kept at a low temperature stage of 900-1020°C for 3-6 hours. At this time, the Ti3Nb precipitates in the magnet are fully grown and distributed in the grain boundary phase of the magnet, and can effectively inhibit the growth of the main phase grains during the subsequent high temperature stage of 1040-1080°C, thereby improving the grain refinement effect of the magnet and improving the magnetic properties of the magnet.

[0028] The invention adds a certain content of Ti and Nb to the raw materials, and adjusts the ratio of Ti and Nb, melts and spins SC sheets, performs high-temperature heat treatment on the SC sheets, performs hydrogen cracking treatment for incomplete hydrogen absorption and air flow grinding to obtain alloy powder, molds the alloy powder in an oriented magnetic field and performs cold isostatic pressing, and prepares the magnet through the steps of segmented vacuum sintering and aging treatment of the molded magnet.

[0029] During the high-temperature heat treatment of the SC sheet, Ti and Nb in the sheet will react to form fine Ti3Nb precipitates. The formation of Ti, Nb and B precipitates can be suppressed by controlling the ratio of Ti and Nb and the heat treatment temperature. In the subsequent hydrogen crushing and air flow milling process, the fine Ti3Nb precipitates will be evenly mixed in the magnetic powder, thereby avoiding the precipitation of Ti3Nb phase inside the main phase grains during sintering. The magnet adopts a staged sintering process, and the Ti3Nb precipitates will further grow to 2~800nm ​​during low-temperature sintering. The Ti3Nb precipitates are small in size and have good dispersibility. When evenly distributed in the grain boundary R-rich phase of the magnet, they can effectively enhance the grain boundary phase of the magnet and improve the strength and toughness of the magnet, thereby preparing a magnet with both high strength and high toughness. The growth of the main phase grains mainly occurs in the high temperature section sintering. Since the Ti3Nb precipitates grow before the main phase grains, the excessive growth of the main phase grains can be effectively suppressed, and the excellent grain refinement effect can be achieved, which can further improve the magnetic properties of the magnet. The beneficial effects of the present invention are: by synergistically adding two high melting point elements, Ti and Nb, and adjusting the ratio of the two elements, combined with the SC sheet high temperature heat treatment, unsaturated hydrogen absorption and segmented vacuum sintering process, the generation of small Ti3Nb phases is promoted while suppressing the precipitation of large-sized high melting point element borides. The small Ti3Nb precipitate particles have better dispersibility, and when evenly distributed in the grain boundary R-rich phase of the magnet, the grain boundary phase of the magnet can be effectively enhanced, while not causing distortion of the main phase, reducing the hardness of the magnet, and improving the strength and toughness of the magnet. The excellent grain refinement effect of Ti3Nb can also improve the magnetic properties of the magnet, thereby preparing a magnet with both high strength and high toughness and excellent magnetic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the microstructure diagram of the SC sheet subjected to high temperature heat treatment in Experiment No. 1 to Experiment No. 3.

[0031] Figure 2 This is the TEM microstructure and selected area electron diffraction pattern of the sintered magnet precipitate from Experiment No. 1.

[0032] Figure 3 This is the TEM microstructure and selected area electron diffraction pattern of the sintered magnet precipitate from Experiment No. 2.

[0033] Figure 4 This is the TEM microstructure and selected area electron diffraction pattern of the sintered magnet precipitate from Experiment No. 3. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0035] The present invention adopts vacuum induction melting and belt throwing, takes raw materials with a purity of more than 99.9% according to the composition ratio, puts them into the crucible in order from high to low melting points, and evacuates the furnace until the vacuum degree reaches 10 -3 ~10 -4 Pa, dew point is lower than -50℃. Then fill the furnace with argon gas to make the pressure reach 30~50kPa, and heat it to 1480~1510℃. After the raw materials are completely melted, keep it warm for 3~5min. Then reduce the temperature of the alloy liquid to 1440~1460℃, and keep it warm and cast it. Adjust the speed of the copper roller to 70~75 rpm, and then rotate the crucible at a certain speed so that the molten alloy liquid is transported to the cooling roller through the tundish for solidification and then falls on the water cooling plate for cooling.

[0036] The SC sheet prepared by smelting is subjected to high temperature heat treatment. The alloy sheet prepared by smelting is placed in a molybdenum boat and placed in a heating furnace. The vacuum degree in the furnace is drawn to 10 -3 ~10 -4 Pa and heat to 800~900℃. When the temperature reaches the target temperature, fill the furnace with argon gas at a pressure of 30~50kPa and keep it warm for 20min~50min. After the heat treatment is completed, cool it to room temperature. There is no requirement for the cooling speed in this process. It can be cooled with the furnace or air cooled.

[0037] The alloy flakes are prepared into alloy powder by hydrogen crushing and air flow milling. During the hydrogen crushing treatment, the hydrogen pressure in the reactor is generally 0.01~0.09MPa. During the hydrogen absorption reaction, the pressure change in the reactor does not exceed 0.5% within 110 minutes, which represents saturated hydrogen absorption. In the present invention, the number of hydrogen absorptions is 0.2~0.8 times the normal saturated hydrogen absorption number. After the hydrogen absorption reaction is completed, the temperature is raised to between 400~600℃ while evacuating, and the temperature is kept for 2~6h to release the hydrogen in the alloy flakes, and then cooled to obtain hydrogen crushed coarse powder. The obtained coarse powder is placed in a jet mill, and in an inert gas atmosphere, the nozzle pressure is adjusted to between 0.6MPa~0.8MPa, and the coarse powder is driven by high-speed gas to collide with each other for crushing. The inert gas is generally an inert gas such as helium and nitrogen.

[0038] After adding lubricant and / or antioxidant to the alloy powder, the alloy powder is molded in an oriented magnetic field, and conventional commercially available magnetic powder protection lubricant or antioxidant can be used. The amount of lubricant added can be 0.01-0.1% of the mass of the alloy powder, and the amount of antioxidant added can be 0.01-0.14% of the mass of the alloy powder.

[0039] The orientation magnetic field is preferably 3-6T, and the molding pressure is 5-7MPa. After orientation molding, the green compact is subjected to cold isostatic pressing at a pressure of 150-180MPa. The density of the green compact after orientation molding is 3.6-4.0g / cm 3The density of the green compact after cold isostatic pressing is about 4.6 g / cm 3 .

[0040] The magnet is sintered to a compact size using a segmented vacuum sintering process, which includes two stages of sintering: low temperature and high temperature. The low temperature stage is sintering the magnet at 900-1020°C for 3-6 hours, and the high temperature stage is sintering the magnet at 1040-1080°C for 3-6 hours.

[0041] The sintered magnet needs to undergo a two-stage aging process. First, the primary aging treatment process is carried out at 700~900℃ for 2~8h, then cooled to below 100℃ at a rate of not less than 20℃ / min, and then heated to 400~600℃ for 2~8h of secondary aging treatment. After the end, it is cooled to below 80℃ at a rate of not less than 30℃ / min.

[0042] After the magnet was crushed, a sample was taken from the center, and the magnet composition was detected by ICP. The magnet microstructure was observed by SEM, and the magnet micro-region composition was analyzed by EPMA. The three-point bending sample was prepared by an inner circle slicer and double-sided grinding. The sample size was 25 (±0.01) mm × 6 (±0.01) mm × 5 (±0.01 mm) in length × width × height, and the sample height direction was parallel to the orientation direction of the magnet. The bending strength of the magnet was measured by the three-point bending method according to GB / T31967.2-2015. Ten samples were measured in each group of experiments and the average value was calculated. The three-point bending indenter was a cylinder with a diameter of 5 mm, the diameter of the two support columns was 5 mm, the span between the fulcrums was 14.5 mm, and the pressing speed of the indenter was 0.1 mm / min. The magnetic properties measurement sample was prepared by wire cutting, double-sided grinding and end grinding. The sample was a φ10 mm × 10 mm cylinder, and the magnetic properties of the magnet were measured by NIM equipment. The magnet toughness was characterized by the vibration weightlessness method provided in patent document CN116223262A. The sample size was 15 (±0.01) mm × 15 (±0.01) mm × 5 (±0.01 mm) in length × width × height, and the sample height direction was parallel to the magnet orientation direction. After the magnet was polished, the magnet hardness was tested with a Vickers hardness tester. The test surface was perpendicular to the magnet orientation direction. Each sample was tested for 10 values ​​and the average value was taken as its hardness value.

[0043] Embodiment 1: For low melting point metals, pure metals with a purity of more than 99.9wt.% are used as raw materials. For elements with a melting point higher than pure iron, alloys of the element and iron are used as raw materials. The elements are placed in the crucible in descending order of melting point, and the furnace is evacuated until the vacuum reaches 10 -4Pa, the dew point is lower than -50℃. Then fill the furnace with argon gas to make the gas pressure reach 30kPa, and heat it to 1490℃. After the raw materials are completely melted, keep it warm for 3 minutes. Then reduce the temperature of the alloy liquid to 1450℃ and cast it. Adjust the speed of the copper roller to 70 rpm, and then rotate the crucible at a certain speed, so that the molten alloy liquid is transported to the cooling roller through the tundish for solidification and then falls on the water cooling plate to cool down, and obtain an alloy sheet with a thickness of 0.28±0.05mm.

[0044] The SC sheet prepared by smelting is subjected to high temperature heat treatment. The alloy sheet prepared by smelting is placed in a molybdenum boat and placed in a heating furnace. The vacuum degree in the furnace is drawn to 10 -3 Pa and heated to 900℃. When the temperature reaches the target temperature, fill the furnace with argon gas at a pressure of 30kPa and keep it warm for 30min. After the heat treatment is completed, cool it to room temperature with the furnace.

[0045] The alloy flakes were subjected to hydrogen absorption reaction under a hydrogen pressure of 0.09 MPa. The saturated hydrogen absorption times of 20 kg of the flakes were 18 times. The unsaturated hydrogen absorption was used in this embodiment, and the hydrogen absorption times were 9 times. After the hydrogen absorption reaction, the temperature was raised to 550°C while evacuating the vacuum, and the temperature was kept for 4 hours to release the hydrogen in the alloy flakes, and then cooled to obtain hydrogen-crushed coarse powder. After cooling, 0.05 wt.% zinc stearate was added to the coarse powder and mixed for 3 hours. The coarse powder was further crushed to obtain fine powder using a nitrogen gas flow mill, and the gas pressure was 0.6 MPa.

[0046] Add 0.03wt.% of organic lubricant (magnetic powder protection lubricant 3# produced by Tianjin Yuesheng New Materials Research Institute) to the fine powder and mix for 3 hours. The fine powder after mixing is oriented and formed under a magnetic field. The orientation magnetic field is a static magnetic field of 3.5T and the pressing pressure is 5MPa. The density of the magnet after pressing is 3.9~4.0g / cm 3 After that, cold isostatic pressing is performed with a pressing pressure of 160MPa. The density of the magnet after pressing is greater than 4.6g / cm 3 .

[0047] The magnet is sintered to a compact size using a segmented vacuum sintering process. The vacuum sintering process has a vacuum degree of 10 -4 Pa, the sintering temperature in the low temperature stage is 1000℃, and the holding time is 3h. After the low temperature stage is finished, the temperature is raised to 1060℃, and the high temperature stage is sintered, and the holding time is 3h.

[0048] The sintered magnet needs to undergo a two-stage aging process. First, the primary aging treatment process is carried out at 880℃ for 3h, then cooled to below 100℃ at a rate of not less than 20℃ / min, and then heated to 500℃ for 3h of secondary aging treatment. After the end, it is cooled to below 80℃ at a rate of not less than 30℃ / min.

[0049] After the magnet is crushed, a sample is taken from the center, and the magnet composition is detected by ICP. The magnet microstructure is observed by SEM, and the magnet micro-region composition and structure are analyzed by TEM. The bending strength of the magnet is measured by the three-point bending method in accordance with GB / T31967.2-2015. Ten samples are measured in each group of experiments and the average value is calculated. The magnetic properties of the magnet are measured by NIM equipment, and the toughness of the magnet is characterized by the vibration weightlessness method provided in patent document CN116223262A. The hardness of the magnet is tested by a Vickers hardness tester.

[0050] The magnet components of each experimental group are expressed in mass fraction, as shown in Table 1: Table 1 No. Nd Pr Dy B Co Cu Ga Al Ti Nb Fe 1 23.3 7.7 0.4 0.95 1.0 0.14 0.2 0.4 0.25 / Bal 2 23.3 7.7 0.4 0.95 1.0 0.14 0.2 0.4 / 0.25 Bal 3 23.3 7.7 0.4 0.95 1.0 0.14 0.2 0.4 0.15 0.1 Bal The magnet properties of each experimental group are shown in Table 2: Table 2 No. Br HkDJ Hk / Hcj 1 13.40 20.3 97.5% 2 13.41 20.4 97.3% 3 13.45 21.1 98.0% The magnets of Experiment No. 1 and Experiment No. 2 were added with Ti and Nb elements respectively, while the magnets of Experiment No. 3 were added with Ti and Nb elements synergistically. From the data in Table 1 and Table 2, it can be seen that the remanence of the magnet of Experiment No. 3 is slightly higher than that of Experiment No. 1 and Experiment No. 2, while the coercive force of the magnet of Experiment No. 3 is significantly higher than that of Experiment No. 1 and Experiment No. 2, indicating that the synergistic addition of Ti and Nb elements can effectively improve the coercive force of the magnet.

[0051] The bending strength, Vickers hardness and vibration weight loss of the magnets in each experimental group are shown in Table 3: Table 3 No. Flexural strength (MPa) Vibration weight loss (%) Hardness (Hv) 1 480.3 0.16 590.1 2 462.5 0.14 582.7 3 512.9 0.08 560.3 It can be seen that the bending strength of the magnet in Experiment No. 3 is significantly higher than that in Experiment No. and Experiment No. 1, indicating that the synergistic addition of Ti and Nb elements can effectively improve the strength of the magnet. From the magnet hardness and vibration weight loss data, it can be seen that the hardness and vibration weight loss of the magnet in Experiment No. 3 are lower than those in Experiment No. 1 and Experiment No. 2. The smaller the vibration weight loss of the magnet, the stronger the magnet absorbs impact energy during the collision, that is, the higher the toughness of the magnet. The present invention uses the synergistic addition of Ti and Nb elements to simultaneously improve the strength and toughness of the magnet.

[0052] Figure 1 The microstructure of the SC sheet after high-temperature heat treatment in Experiment No. 1 to Experiment No. 3. Experiment No. 1 only added Ti element, and long fibrous precipitates were precipitated in the grain boundary phase of the SC sheet after high-temperature heat treatment. The precipitates of the SC sheet of Experiment No. 2 were blocky in shape, while the precipitates of the SC sheet of Experiment No. 3 were fine flocs. These precipitates were fully mixed with the magnetic powder in the subsequent hydrogen crushing and air flow milling process, distributed in the grain boundary phase of the magnet, which could improve the mechanical properties of the magnet and refine the main phase grains.

[0053] Figure 2~Figure 4 The TEM microstructures and selected area electron diffraction of the precipitates of the sintered magnets of Experiment No. 1 to Experiment No. 3 are respectively. In Experiment No. 1, only Ti element was added to the magnet, and the precipitates in the sintered magnet were rod-shaped. The selected area electron diffraction results showed that the precipitates were TiB2. In Experiment No. 2, only Nb element was added to the magnet, and the precipitates were mainly block-shaped. The selected area electron diffraction results showed that the precipitates were NbFeB. In Experiment No. 3, Ti and Nb elements were added synergistically. From the TEM microstructure, it can be seen that the precipitates in the sintered magnet are in the form of fine particles, distributed in the two main phase grain boundaries and multi-main phase grain boundaries of the magnet. The size of the particles is below 100nm, which is much smaller than the size of the particles in Experiment No. 1 and Experiment No. 2. The selected area electron diffraction results show that the precipitate is Ti3Nb. The fine Ti3Nb precipitates have better dispersibility and are distributed in the two-phase grain boundaries and multi-phase grain boundaries of the magnet, which can significantly strengthen the grain boundary of the magnet without causing the main phase distortion and reducing the hardness of the magnet. Thus, the magnet can be strengthened and toughened at the same time, and RTB rare earth permanent magnets with both high strength and high toughness can be prepared.

[0054] Embodiment 2: For low melting point metals, pure metals with a purity of more than 99.9wt.% are used as raw materials. For elements with a melting point higher than pure iron, alloys of the element and iron are used as raw materials. The elements are placed in the crucible in descending order of melting point, and the furnace is evacuated until the vacuum reaches 10 -4 Pa, the dew point is lower than -50℃. Then fill the furnace with argon gas to make the gas pressure reach 30kPa, and heat it to 1490℃. After the raw materials are completely melted, keep it warm for 3 minutes. Then reduce the temperature of the alloy liquid to 1450℃ and cast it. Adjust the speed of the copper roller to 70 rpm, and then rotate the crucible at a certain speed, so that the molten alloy liquid is transported to the cooling roller through the tundish for solidification and then falls on the water cooling plate to cool down, and obtain an alloy sheet with a thickness of 0.28±0.05mm.

[0055] The SC sheet prepared by smelting is subjected to high temperature heat treatment. The alloy sheet prepared by smelting is placed in a molybdenum boat and placed in a heating furnace. The vacuum degree in the furnace is drawn to 10 -3 Pa and heated to 900℃. When the temperature reaches the target temperature, fill the furnace with argon gas at a pressure of 30kPa and keep it warm for 30min. After the heat treatment is completed, cool it to room temperature with the furnace.

[0056] The alloy flakes were subjected to hydrogen absorption reaction under a hydrogen pressure of 0.09 MPa. The saturated hydrogen absorption times of 20 kg of the flakes were 18 times. The unsaturated hydrogen absorption was used in this embodiment, and the hydrogen absorption times were 9 times. After the hydrogen absorption reaction, the temperature was raised to 550°C while evacuating the vacuum, and the temperature was kept for 4 hours to release the hydrogen in the alloy flakes, and then cooled to obtain hydrogen-crushed coarse powder. After cooling, 0.05 wt.% zinc stearate was added to the coarse powder and mixed for 3 hours. The coarse powder was further crushed to obtain fine powder using a nitrogen gas flow mill, and the gas pressure was 0.6 MPa.

[0057] Add 0.03wt.% of organic lubricant (magnetic powder protection lubricant 3# produced by Tianjin Yuesheng New Materials Research Institute) to the fine powder and mix for 3 hours. The fine powder after mixing is oriented and formed under a magnetic field. The orientation magnetic field is a static magnetic field of 3.5T and the pressing pressure is 5MPa. The density of the magnet after pressing is 3.9~4.0g / cm 3 After that, cold isostatic pressing is performed with a pressing pressure of 160MPa. The density of the magnet after pressing is greater than 4.6g / cm 3 .

[0058] The magnet is sintered to a compact size using a segmented vacuum sintering process. The vacuum sintering process has a vacuum degree of 10 -4 Pa, the sintering temperature in the low temperature stage is 1000℃, and the holding time is 3h. After the low temperature stage is finished, the temperature is raised to 1060℃, and the high temperature stage is sintered, and the holding time is 3h.

[0059] The sintered magnet needs to undergo a two-stage aging process. First, the primary aging treatment process is carried out at 880℃ for 3h, then cooled to below 100℃ at a rate of not less than 20℃ / min, and then heated to 500℃ for 3h of secondary aging treatment. After the end, it is cooled to below 80℃ at a rate of not less than 30℃ / min.

[0060] After the magnet is broken, a sample is taken from the center and the magnet composition is detected by ICP. The magnet microstructure is analyzed by SEM and the 1mm 2 The proportion of high melting point element borides to high melting point element precipitates within the range. The bending strength of the magnet is measured by the three-point bending method in accordance with GB / T31967.2-2015. Ten samples are measured in each group of experiments and the average value is calculated. The magnetic properties of the magnet are measured using NIM equipment, and the toughness of the magnet is characterized according to the vibration weightlessness method provided in patent document CN116223262A. The hardness of the magnet is tested using a Vickers hardness tester.

[0061] The magnet components of each experimental group are expressed in mass fraction, as shown in Table 4: Table 4 No. Nd Tb B Co Cu Ga Ti Nb Fe 4 30.25 0.3 0.95 0.5 0.2 0.3 0.35 0.20 Bal 5 30.25 0.3 0.95 0.5 0.2 0.3 0.35 0.05 Bal 6 30.25 0.3 0.95 0.5 0.2 0.3 0.50 0.25 Bal The magnet properties of each experimental group are shown in Table 5: Table 5 No. Br HkDJ Hk / Hcj 4 14.40 13.5 98.1% 5 14.35 12.6 97.6% 6 14.20 11.5 89.7% The bending strength, Vickers hardness and vibration weight loss of the magnets in each experimental group are shown in Table 6: Table 6 No. Flexural strength (MPa) Vibration weight loss (%) Hardness (Hv) 4 462.3 0.12 540.6 5 425.6 0.20 590.6 6 380.6 0.35 634.3 The ratio of the amount of high melting point element borides to the amount of precipitates in the magnets of each experimental group is shown in Table 7: Table 7 No. Boride ratio (%) 4 2.1% 5 20.6% 6 3.8% In this embodiment, the content and ratio of Ti and Nb elements in the magnet of Experiment No. 4 meet the requirements of the present invention, so the magnet has high strength and toughness. The content of Ti and Nb elements in the magnet of Experiment No. 5 is within the requirements of the present invention, but the content of Ti and Nb does not meet the ratio requirement of [Ti] / 47.87≤4×[Nb] / 92.91. It can be seen from the data in Table 7 that the proportion of high melting point element boride (TiB2) in the precipitate of the magnet of Experiment No. 5 is relatively large. In the present invention, a certain amount of Nb element needs to be added to promote the formation of Ti3Nb phase and inhibit the precipitation of TiB2. In Experiment No. 5, the addition of Nb element is small, and the Ti element cannot fully form the Ti3Nb phase, so the residual Ti will react with the B element of the magnet to form TiB2. The size of the TiB2 precipitate is large, and the large size of the precipitate distributed near the main phase grains will cause stress concentration near the main phase grains, and the main phase grains will be distorted, so the hardness of the magnet is relatively large. In addition, the coarse precipitates have poor dispersion and distribution, and the strengthening effect on the magnet is poor, so the strength and toughness of the magnet are lower than those of the magnet in Experiment No. 4. In addition, due to the precipitation of more TiB2, more B elements are consumed, resulting in a decrease in the proportion of the main phase of the magnet, so the remanence of the final magnet decreases.

[0062] The content ratio of Ti and Nb elements in the magnet of Experiment No. 6 meets the ratio requirement of [Ti] / 47.87≤4×[Nb] / 92.91, but too much high melting point element Ti is added to the magnet, exceeding the range of 0.1~0.4wt.%, which makes it difficult to sinter the magnet densely and reduces the mechanical properties of the material. At the same time, the presence of too much non-magnetic phase will reduce the remanence of the magnet, so the magnetic properties and mechanical properties of the magnet of Experiment No. 6 are at a low level.

[0063] Embodiment three: For low melting point metals, pure metals with a purity of more than 99.9wt.% are used as raw materials. For elements with a melting point higher than pure iron, alloys of the element and iron are used as raw materials. The elements are placed in the crucible in descending order of melting point, and the furnace is evacuated until the vacuum reaches 10 -4Pa, dew point is lower than -50℃. Then fill the furnace with argon gas to make the gas pressure reach 30kPa, and heat it to 1490℃. After the raw materials are completely melted, keep it warm for 3 minutes. Then reduce the temperature of the alloy liquid to 1450℃ and cast it. Adjust the speed of the copper roller to 70 rpm, and then rotate the crucible at a certain speed, so that the molten alloy liquid is transported to the cooling roller through the tundish for solidification and then falls on the water cooling plate to cool down, and obtain an alloy sheet with a thickness of 0.30±0.05mm.

[0064] The SC sheet prepared by smelting is subjected to high temperature heat treatment. The alloy sheet prepared by smelting is placed in a molybdenum boat and placed in a heating furnace. The vacuum degree in the furnace is drawn to 10 -3 Pa and heated to 900 ° C. When the temperature reaches the target temperature, fill the furnace with argon gas at a pressure of 30 kPa and keep it warm for 30 minutes. After the heat treatment is completed, cool it to room temperature with the furnace. In this embodiment, Experiment No. 7 and Example 9 use the SC sheet heat treatment process, while Experiment No. 8 does not use the SC sheet heat treatment process.

[0065] The alloy flakes were subjected to hydrogen absorption reaction under a hydrogen pressure of 0.09 MPa. The saturated hydrogen absorption times of 20 kg of the flakes were 18 times. The unsaturated hydrogen absorption was used in this embodiment, and the hydrogen absorption times were 9 times. After the hydrogen absorption reaction, the temperature was raised to 550°C while evacuating the vacuum, and the temperature was kept for 4 hours to release the hydrogen in the alloy flakes, and then cooled to obtain hydrogen-crushed coarse powder. After cooling, 0.05 wt.% zinc stearate was added to the coarse powder and mixed for 3 hours. The coarse powder was further crushed to obtain fine powder using a nitrogen gas flow mill, and the gas pressure was 0.6 MPa.

[0066] Add 0.03wt.% of organic lubricant (magnetic powder protection lubricant 3# produced by Tianjin Yuesheng New Materials Research Institute) to the fine powder and mix for 3 hours. The fine powder after mixing is oriented and formed under a magnetic field. The orientation magnetic field is a static magnetic field of 3.5T and the pressing pressure is 5MPa. The density of the magnet after pressing is 3.9~4.0g / cm 3 After that, cold isostatic pressing is performed with a pressing pressure of 160MPa. The density of the magnet after pressing is greater than 4.6g / cm 3 .

[0067] The magnet is sintered to a compact size using a segmented vacuum sintering process. The vacuum sintering process has a vacuum degree of 10 -4 Pa, the low temperature stage sintering temperature is 1000℃, and the holding time is 3h. After the low temperature stage is finished, the temperature is raised to 1060℃, and the high temperature stage sintering is carried out, and the holding time is 3h. In this embodiment, the magnets of Experiment No.7 and Experiment No.8 adopt a two-stage sintering process. Experiment No.9 does not adopt a two-stage sintering process, and directly heats up to 1060℃ and holds for 6h.

[0068] The sintered magnet needs to undergo a two-stage aging process. First, the primary aging treatment process is carried out at 880℃ for 3h, then cooled to below 100℃ at a rate of not less than 20℃ / min, and then heated to 500℃ for 3h of secondary aging treatment. After the end, it is cooled to below 80℃ at a rate of not less than 30℃ / min.

[0069] After the magnet is crushed, a sample is taken from the center, the magnet composition is detected by ICP, and the magnet microstructure is observed by SEM. The bending strength of the magnet is measured by the three-point bending method in accordance with GB / T31967.2-2015. Ten samples are measured in each group of experiments and the average value is calculated. The magnetic properties of the magnet are measured by NIM equipment, and the toughness of the magnet is characterized by the vibration weightlessness method provided in patent document CN116223262A. The hardness of the magnet is tested by a Vickers hardness tester.

[0070] The processes used for magnets in different experimental groups are shown in Table 8: Table 8 No. SC sheet heat treatment Two-stage sintering process 7 √ √ 8 × √ 9 √ × The magnet components of each experimental group are expressed in mass fraction, as shown in Table 9: Table 9 No. Nd Tb B Co Cu Ga Ti Nb Fe 7 30.25 0.3 0.95 0.5 0.2 0.3 0.35 0.20 Bal 8 30.25 0.3 0.95 0.5 0.2 0.3 0.35 0.20 Bal 9 30.25 0.3 0.95 0.5 0.2 0.3 0.35 0.20 Bal The magnet properties of each experimental group are shown in Table 10: Table 10 No. Br HkDJ Hk / Hcj 7 14.40 13.5 98.1% 8 14.40 12.6 97.6% 9 14.40 12.3 97.6% The bending strength, Vickers hardness and vibration weight loss of the magnets in each experimental group are shown in Table 11: Table 11 No. Flexural strength (MPa) Vibration weight loss (%) Hardness (Hv) 7 462.3 0.12 540.6 8 440.3 0.16 568.5 9 451.8 0.14 552.3 From the data in Table 9, it can be seen that the SC sheet heat treatment and two-stage sintering process will not affect the composition of the magnet. However, the results in Table 10 show that there are obvious differences in the magnetic properties of the final magnets. The coercive forces of the magnets of Experiment No. 8 and No. 9 are lower than that of Experiment No. 7. By counting the grain sizes of the magnets of Experiment No. 7 to Experiment No. 9, it is found that the average grain size of the magnet of Experiment No. 7 is 4.6μm, while the average grain sizes of the magnets of Experiment No. 8 and Experiment No. 9 are 5.1μm and 5.3μm, respectively. This shows that the use of SC sheet heat treatment and two-stage sintering process can significantly refine the grains, thereby improving the coercive force of the magnet.

[0071] From the data in Table 11, it can be seen that the bending strength of the magnets of Experiment No. 8 and Experiment No. 9 is significantly lower than that of Experiment No. 7, and the vibration weight loss is higher than that of Experiment No. 7, indicating that the strength and toughness of the magnets of Experiment No. 8 and Experiment No. 9 are at a lower level than that of Experiment No. 7. By statistically analyzing the distribution of high melting point element precipitates in the magnets, the results are shown in Table 12: Table 12 No. The proportion of R-rich Ti3Nb distributed at the grain boundary 7 99.8% 8 90.2% 9 93.1% As can be seen from Table 12, most of the Ti3Nb precipitates in the magnet of Experiment No. 7 are distributed in the R-rich phase at the grain boundary of the magnet. In the magnets of Experiment No. 8 and Experiment No. 9, a large number of Ti3Nb precipitates are distributed inside the main phase grains of the magnet. Since Ti3Nb is a high-melting-point element precipitate, its wettability with the main phase of the magnet is poor, and the interface between the two phases is a natural crack source, resulting in poor mechanical properties of the magnets of Experiment No. 8 and Experiment No. 9. In the present invention, the SC sheet heat treatment process is used to make the Ti3Nb precipitates precipitate in the SC sheet stage, and the Ti3Nb precipitates are evenly mixed with the magnetic powder after hydrogen breaking and air flow grinding. In the subsequent sintering process, a two-stage sintering process is used to make the Ti3Nb precipitates distributed in the grain boundary phase of the magnet grow preferentially. The growth of precipitates before the main phase grains can effectively refine the grains, avoid the merging and growth of the main phase, and the precipitation of Ti3Nb inside the main phase grains. Therefore, in the present invention, it is preferred to adopt the SC sheet heat treatment process and the two-stage sintering process.

[0072] Embodiment 4: For low melting point metals, pure metals with a purity of more than 99.9wt.% are used as raw materials. For elements with a melting point higher than pure iron, alloys of the element and iron are used as raw materials. The elements are placed in the crucible in descending order of melting point, and the furnace is evacuated until the vacuum reaches 10 -4 Pa, the dew point is lower than -50℃. Then fill the furnace with argon gas to make the gas pressure reach 30kPa, and heat it to 1490℃. After the raw materials are completely melted, keep it warm for 3 minutes. Then reduce the temperature of the alloy liquid to 1450℃ and cast it. Adjust the speed of the copper roller to 70 rpm, and then rotate the crucible at a certain speed, so that the molten alloy liquid is transported to the cooling roller through the tundish for solidification and then falls on the water cooling plate to cool down, and obtain an alloy sheet with a thickness of 0.28±0.05mm.

[0073] The SC sheet prepared by smelting is subjected to high temperature heat treatment. The alloy sheet prepared by smelting is placed in a molybdenum boat and placed in a heating furnace. The vacuum degree in the furnace is drawn to 10 -3 Pa and heated to 900℃. When the temperature reaches the target temperature, fill the furnace with argon gas at a pressure of 30kPa and keep it warm for 30min. After the heat treatment is completed, cool it to room temperature with the furnace.

[0074] The alloy flakes were subjected to hydrogen absorption reaction under a hydrogen pressure of 0.09MPa. The saturated hydrogen absorption times of 20 kg of the flakes were 24 times. Experiment No. 11 used unsaturated hydrogen absorption, and the number of hydrogen absorption times was 10 times; Experiment No. 12 used saturated hydrogen absorption, and the number of hydrogen absorption times was 24 times. After the hydrogen absorption reaction, the temperature was raised to 550℃ while vacuuming, and the temperature was kept for 4 hours to release the hydrogen in the alloy flakes, and then cooled to obtain hydrogen-crushed coarse powder. After cooling, 0.05wt.% zinc stearate was added to the coarse powder and mixed for 3 hours. The coarse powder was further crushed to obtain fine powder using a nitrogen gas flow mill, and the gas pressure was 0.6MPa.

[0075] Add 0.03wt.% of organic lubricant (magnetic powder protection lubricant 3# produced by Tianjin Yuesheng New Materials Research Institute) to the fine powder and mix for 3 hours. The fine powder after mixing is oriented and formed under a magnetic field. The orientation magnetic field is a static magnetic field of 3.5T and the pressing pressure is 5MPa. The density of the magnet after pressing is 3.9~4.0g / cm 3 After that, cold isostatic pressing is performed with a pressing pressure of 160MPa. The density of the magnet after pressing is greater than 4.6g / cm 3 .

[0076] The magnet is sintered to a compact size using a segmented vacuum sintering process. The vacuum sintering process has a vacuum degree of 10 -4 Pa, the sintering temperature of the low temperature stage is 950℃, and the holding time is 4.5h. After the low temperature stage is finished, the temperature is raised to 1050℃, and the high temperature stage is sintered, and the holding time is 4.5h.

[0077] The sintered magnet needs to undergo a two-stage aging process. First, the primary aging treatment process is carried out at 880℃ for 3h, then cooled to below 100℃ at a rate of not less than 20℃ / min, and then heated to 500℃ for 3h of secondary aging treatment. After the end, it is cooled to below 80℃ at a rate of not less than 30℃ / min.

[0078] After the magnet is broken, a sample is taken from the center and the magnet composition is detected by ICP. The magnet microstructure is observed by SEM and the 1mm 2 The number of high melting point element precipitates within the range. The bending strength of the magnet was measured by the three-point bending method according to GB / T31967.2-2015. Ten samples were measured in each experiment and the average value was calculated. The magnetic properties of the magnet were measured using NIM equipment, and the toughness of the magnet was characterized according to the vibration weightlessness method provided in patent document CN116223262A. The hardness of the magnet was tested using a Vickers hardness tester.

[0079] The magnet components of each experimental group are expressed in mass fraction, as shown in Table 13: Table 13 No. Nd Pr B Co Al Cu Ga Dy Ti Nb Fe 11 20.6 6.5 0.92 1.0 0.2 0.2 0.3 1.9 0.18 0.1 Bal 12 20.6 6.5 0.92 1.0 0.2 0.2 0.3 1.9 0.16 0.09 Bal The bending strength, Vickers hardness and vibration weight loss of the magnets in each experimental group are shown in Table 14: Table 14 No. Flexural strength (MPa) Vibration weight loss (%) Hardness (Hv) 11 496.3 0.11% 580.3 12 471.0 0.12% 583.6 As shown in Table 13, the saturated hydrogen absorption process was used in the preparation of Experiment No. 12, and the content of Ti and Nb elements in the final sintered magnet was lower than that of Experiment No. 11, indicating that the loss of Ti and Nb elements in the magnet preparation process of Experiment No. 12 was greater. Comparing the mechanical properties of the magnets of Experiment No. 11 and Experiment No. 12, the hardness and vibration weight loss of the magnets in the two experimental groups are basically the same, but the bending strength of the magnet of Experiment No. 12 is lower than that of Experiment No. 11.

[0080] In the present invention, the Ti3Nb phase will precipitate in the grain boundary phase during the high temperature heat treatment of the SC sheet. When the saturated hydrogen absorption is used in the hydrogen crushing stage, the grain boundary phase will be over-crushed, resulting in a large loss of Ti3Nb compounds distributed in the grain boundary phase during the jet milling stage as the ultrafine powder is separated. This ultimately results in a reduction in the number of Ti3Nb precipitates in the magnet, and a reduction in the strengthening and toughening effect of Ti3Nb on the magnet. Therefore, an unsaturated hydrogen absorption process is used in the present invention.

Claims

1. A high-strength and high-toughness RTB rare earth permanent magnet, characterized in that The magnet composition comprises the following components: R: 28.5wt.%~34.0wt.%, R includes one or more elements selected from Nd, Pr, Dy, Tb, Ho, Gd, La, Ce, Lu, and Y; and R contains at least R1 element, and the R1 element is one or more of Nd, Pr, and Ce; B: 0.85~1.1wt.%, Ti: 0.1~0.4wt.%, Nb: 0.05~0.5wt.%, M: 0.01-8.0wt.%, M is at least one of Al, Cu, Ga, Ni, Zn, Sn, Mn, and Zr, The balance is T and other unavoidable impurities, where T is Fe or Fe and Co, and more than 85.0% of the mass fraction of T is Fe; And satisfy: [Ti] / 47.87≤4×[Nb] / 92.91, wherein [Ti] is the content of Ti expressed in mass fraction, and [Nb] is the content of Nb expressed in mass fraction; The magnet contains Ti3Nb precipitates, and more than 99% of the Ti3Nb precipitates are distributed in the R-rich phase at the grain boundaries of the magnet.

2. The high-strength and high-toughness RTB rare earth permanent magnet according to claim 1, characterized in that The size of the Ti3Nb precipitates is between 2 and 800 nm.

3. The high-strength and high-toughness RTB rare earth permanent magnet according to claim 1, characterized in that The Ti3Nb precipitates are distributed on the two-main-phase grain boundaries and the multi-main-phase grain boundaries of the magnet.

4. The high-strength and high-toughness RTB rare earth permanent magnet according to claim 1, characterized in that The magnet includes high melting point element precipitates, which include Ti3Nb precipitates and borides of Ti and Nb. The amount of borides of Ti and Nb in a cross section of the magnet in any direction is less than 5% of the amount of high melting point element precipitates.

5. The high-strength and high-toughness RTB rare earth permanent magnet according to any one of claims 1 to 4, characterized in that The high-strength and high-toughness RTB rare earth permanent magnet is prepared according to the following method: raw materials are taken according to a ratio and vacuum induction melting and belt spinning are used to prepare SC sheets, the SC sheets are subjected to high-temperature heat treatment, the SC sheets after high-temperature heat treatment are subjected to hydrogen cracking treatment for unsaturated hydrogen absorption and air flow grinding to obtain alloy powder, the alloy powder is molded in an oriented magnetic field and cold isostatically pressed, and the obtained molded magnet is subjected to segmented vacuum sintering and aging treatment to obtain the high-strength and high-toughness RTB rare earth permanent magnet.

6. The method for preparing the high-strength and high-toughness RTB rare earth permanent magnet according to any one of claims 1 to 4, characterized in that The method comprises the following steps: raw materials are taken according to a ratio, and SC sheets are prepared by vacuum induction melting and belt spinning; the SC sheets are subjected to high-temperature heat treatment; the SC sheets after the high-temperature heat treatment are subjected to hydrogen cracking treatment for unsaturated hydrogen absorption and air flow grinding to obtain alloy powder; the alloy powder is molded in an oriented magnetic field and cold isostatically pressed; the obtained molded magnets are subjected to segmented vacuum sintering and aging treatment to obtain the high-strength and high-toughness RTB rare earth permanent magnets.

7. The method according to claim 6, characterized in that The high temperature heat treatment of the SC sheet refers to keeping the SC sheet in an argon environment at 800-900° C. for 20-50 minutes, with the argon pressure being 30-50 kPa.

8. The method according to claim 6, characterized in that The unsaturated hydrogen absorption means that the number of hydrogen absorption is 0.2 to 0.8 times the number of saturated hydrogen absorption; the saturated hydrogen absorption number is obtained by testing according to the following method: SC sheets of the same specification and weight are placed in a reactor, and after evacuation, hydrogen is filled with a positive pressure of 0.1 MPa. The positive pressure refers to the difference between the absolute pressure and the standard atmospheric pressure. The hydrogen absorption of the SC sheet causes the hydrogen pressure in the reactor to decrease, and the positive pressure in the reactor is reduced to 0.05 to 0.06 MPa. Hydrogen is filled into the reactor again until the positive pressure is 0.1 MPa. Each hydrogen filling action is counted as one hydrogen absorption number; after multiple hydrogen absorptions, after a certain hydrogen filling, the pressure change within 10 minutes is less than 0.5%, indicating that the SC sheet is saturated with hydrogen absorption, and the total number of hydrogen fillings at this time is the saturated hydrogen absorption number.

9. The method according to claim 6, characterized in that The segmented vacuum sintering includes low-temperature segment sintering and high-temperature segment sintering. The low-temperature segment sintering is carried out at a temperature of 900-1020°C for 3-6 hours, and the high-temperature segment sintering is carried out at a temperature of 1040-1080°C for 3-6 hours. The vacuum degree of the segmented vacuum sintering is 10 -4 Below Pa.

10. The method according to claim 6, characterized in that The aging treatment refers to a primary aging treatment process in which the sintered magnet is subjected to a temperature of 700-900°C for 2-8 hours, then cooled to below 100°C at a rate of not less than 20°C / min, and then heated to 400-600°C for a secondary aging treatment of 2-8 hours, and then cooled to below 80°C at a rate of not less than 30°C / min.

Citation Information

Cited By

  • Neodymium iron boron magnet and its preparation method

    CN119964920B